Psychiatric Symptoms of Patients With Anti-NMDA Receptor Encephalitis - Wang, Wei; Zhang, Le; Chi, Xiao-Sa; He, Li; Zhou, Dong; Li, Jin-Mei (Frontiers in Neurology, 2020)
Objective: We conducted this study to analyze the clinical characteristics of the psychiatric symptoms of patients with anti-NMDAR encephalitis. Methods: A retrospective study of anti-NMDAR encephalitis in China was performed. The clinical characteristics of the psychiatric symptoms, the relationship between the antibodies titers and clinical characteristics of patients with anti-NMDAR encephalitis were determined. Results: A total of 108 patients with a definitive diagnosis of anti-NMDAR encephalitis were included in this study. 103 patients (95%) developed one or several psychiatric symptoms. The comparison of the high titer group and the low titer group showed that more patients presented psychiatric symptoms as the initial symptom in the high titer group (P = 0.020), the prevalence of the symptoms such as depressive, catatonic and central hypoventilation were also higher in the high titer group than the low titer group (P = 0.033, 0.031 and 0.006, respectively). Meanwhile, more patients received a combination treatment of IVIg and corticosteroids in the high titer group than the low titer group and patients in high titer group were prescript with anti-psychiatric drugs more often than the patients in low titer group (P = 0.026 and 0.003, respectively). Conclusions: Psychiatric symptoms are the most common clinical characteristics of patients with anti-NMDAR encephalitis. Patients with higher antibodies titers more often presented with psychiatric symptoms as the initial symptom, and showed a more severe clinical feature. Screening for the anti-NMDAR antibodies is essentially important in patients who present psychiatric symptoms with or without other neurological symptoms.